CORPORATE GOVERNANCE, FIRMS’ FINANCIAL PERFORMANCE AND SHAREHOLDERS’ CONFIDENCE: ANALYSES OF CHANGES IN GOVERNANCE CODE - UR RAHMAN, HASEEB (2017)
After the Asian financial crisis in 1997-98, the global financial crisis 2007-08 was the biggest turmoil that badly affected shareholders’ confidence in Malaysia. In addition, some domestic corporate failures in 2008 and 2010 further traumatized the already shaken confidence of shareholders in the country. Subsequently, despite 17 new listings, the total market valuation of Bursa Malaysia decreased from RM 1,275.3 billion in 2010 to RM 1,255.93 billion in 2011. To cope with this challenge, the Securities Commission Malaysia reinforces independence in structure and composition of the board by introducing a new code of Corporate Governance (CG) - Malaysian Code on Corporate Governance (MCCG) in March, 2012. Thus, this study has a motivation to investigate the impact of the new code as the introduction or revision of regulations is a time consuming and costly activity. Due to shareholders’ primary interest in the maximization of their wealth and thus firms’ profitability, this study aimed to investigate the impact of the new code on the level of compliance to some specific CG attributes, and their impact on firms’ financial performance and shareholders’ confidence. The comparison of a stratified random sample composed of 320 non-financial listed companies in two years (2010-11) pre and two years (2013-14) post-context of the code revealed magnification in the level of compliance to all CG attributes included in the study. By employing Ordinary Least Squares with Panel Corrected Standard Errors (OLS-PCSEs), it is also found that the significant positive role of board independent chair and senior and women directors have pronounced in relation to ROE and shareholders’ confidence after enactment of the code. Besides literature, the study also contributes to the agency theory by investigating the novel mediating effect of ROE in the relationship between specific CG attributes and shareholders’ confidence. Overall, the study provides important insights for academia, regulators, policy makers, institutions, and shareholders in Malaysia and other developing countries of the world.